Safety systems, culture, and willingness to fly in autonomous air taxis: A multi-study and mediation analysis. (March 2021) - Ward, Kenneth A.; Winter, Scott R.; Cross, David S.; Robbins, John M.; Mehta, Rian; Doherty, Shawn; Rice, Stephen
Highlights: ● Studied effects of systems & nationality on willingness to fly autonomous aircraft indians were more willing to fly in autonomous aircraft than Americans. ●People were more willing to fly in an aircraft equipped with an airframe parachute. ●Americans, not Indians, increased willingness with airframe parachute availability. ●Cultural orientation did not mediate the relationship.